Faktor-faktor yang Mempengaruhi Kesadaran Penderita Diabetes Mellitus terhadap Komplikasi Retinopati Diabetik - Nur Ila; Elly L Sjattar; Andina Setyawati (Journal of Telenursing (JOTING), 2023)
This research aims to analyze the factors that influence DM sufferers' awareness of Diabetic Retinopathy complications. The research method used is an integrative review through 5 stages, namely problem identification, literature search, data evaluation, data analysis and presentation of findings. The research results show that lack of information about RD, lack of knowledge in carrying out eye examinations, lack of health insurance, are among the causes of the low level of awareness of DM sufferers regarding RD complications. Meanwhile, DM sufferers' awareness of RD complications is influenced by the fear of blindness as a complication of untreated RD. In conclusion, the government and health service providers need to adapt interventions and specifically increase the knowledge of DM sufferers about DM disease itself and its complications, especially RD, so that it is handled well so that permanent blindness can be prevented. Keywords: Diabetes Mellitus, Awareness, Diabetic Retinopathy